2011
DOI: 10.1002/asia.201000677
|View full text |Cite
|
Sign up to set email alerts
|

Arginine‐Facilitated α‐ and π‐Radical Migrations in Glycylarginyltryptophan Radical Cations

Abstract: We have used model tripeptides GXW (with X being one of the amino acid residues glycine (G), alanine (A), leucine (L), phenylalanine (F), glutamic acid (E), histidine (H), lysine (K), or arginine (R)) to study the effects of the basicity of the amino acid residue on the radical migrations and dissociations of odd-electron molecular peptide radical cations M(·+) in the gas phase. Low-energy collision-induced dissociation (CID) experiments revealed that the interconvertibility of the isomers [G(·)XW](+) (radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 70 publications
5
59
0
Order By: Relevance
“…This trend was consistently observed for over 20 singly protonated peptide sulfinyl radical ions. Similar phenomenon was observed for CID of arginine containing tripeptide radical cations [66][67][68]. Theoretical calculations by Zhao et al showed that the energy barriers for radical migration were lowered by 5-10 kcal/mol due to localization of charge on arginine sidechain, while the charge-directed dissociation barriers were increased significantly [67].…”
Section: Unimolecular Dissociation Of Peptide Sulfinyl Radical Cationssupporting
confidence: 70%
“…This trend was consistently observed for over 20 singly protonated peptide sulfinyl radical ions. Similar phenomenon was observed for CID of arginine containing tripeptide radical cations [66][67][68]. Theoretical calculations by Zhao et al showed that the energy barriers for radical migration were lowered by 5-10 kcal/mol due to localization of charge on arginine sidechain, while the charge-directed dissociation barriers were increased significantly [67].…”
Section: Unimolecular Dissociation Of Peptide Sulfinyl Radical Cationssupporting
confidence: 70%
“…: the CID mass spectrum of the Arg-containing peptide is dominated by side chain losses and c/z fragments, whereas that of the Lys-containing peptide is dominated by the y 10 fragment. Theoretical calculations of GRW radical cations by Chu and co-workers revealed that the presence of arginine facilitated radical migration [48]. The CID spectra of [G…”
Section: Losses Ofmentioning
confidence: 99%
“…Fragmentation pathways of hydrogen-deficient species in ECD were distinct from those observed in CID, IRMPD, and EID of the same species [21]. In general, in CID, IRMPD, and EID of highly charged hydrogen-deficient species fragmentation is governed by a competition between radical and chargedriven processes [10][11][12][13][14][15]21]. Abundant amino acid sidechain losses, enhanced cleavages at aromatic residues, and formation of a-, b-, c-, y-, c-, and z-type ions are observed [5,16,[20][21][22].…”
Section: Discussionmentioning
confidence: 80%
“…Dissociation of hydrogen-deficient species is determined by the competition between radical and charge driven processes [10][11][12][13][14][15]. For singly charged arginine containing radical cations, M +• , dissociation is governed by radical driven processes resulting mainly in C a -C bond cleavages and side chain losses [12,13,16].…”
Section: Introductionmentioning
confidence: 99%